A Facile Synthesis of Granular ZnO Nanostructures for Dye-Sensitized Solar Cells - Md. Mahbubur Rahman; Narayan Chandra Deb Nath; Kwang-Mo Noh; Jaecheon Kim; Jae-Joon Lee (International Journal of Photoenergy)
Granular ZnO nanostructures of single-crystalline wurtzite hexagonal phases were synthesized by a facile and low-cost chemical method in aqueous condition. The average size of ZnO nanograin increased with reflux time, and it significantly affected the open circuit potential (Voc) while the short circuit current density (Jsc) was not changed much. The overall energy conversion efficiency was 1.82% with the smaller grain size of ca. 250 nm when it was used as photoelectrode of DSSCs. The positive shifting of the Fermi energy (EF) and low density of surface states (DOS) were consistent with the reduction of the recombination of excited electron with electrolyte for smaller grains.